A porous Ru nanomaterial as an efficient electrocatalyst for the hydrogen evolution reaction under acidic and neutral conditions. Issue 85 (12th October 2017) - Drouet, S.; Creus, J.; Collière, V.; Amiens, C.; García-Antón, J.; Sala, X.; Philippot, K.
Abstract : A porous Ru nanomaterial exhibits high electrocatalytic performance and excellent durability for the hydrogen evolution reaction (HER) under both acidic and neutral conditions. Abstract : A porous Ru nanomaterial exhibits high electrocatalytic performance and excellent durability for the hydrogen evolution reaction (HER) under both acidic and neutral conditions. It displays a low overpotential of 83 mV at a current density of 10 mA cm −2 and an excellent durability up to 12 h in 0.5 M H2 SO4 .